Presence of foodborne pathogens and survival of generic Escherichia coli in an organic integrated crop-livestock system - Cheong, Sejin; Jay-Russell, Michele T.; Chandler-Khayd, Carolyn; Di Francesco, Juliette; Haghani, Viktoria; Aminanadi, Peiman; Williams, Sequoia R.; Gaudin, Amélie C. M.; Tautges, Nicole; Pires, Alda F. A. (Frontiers in Sustainable Food Systems, 2024)
Introduction Integrated crop-livestock systems (ICLS) use animals to graze crop residues or cover crops before planting fresh produce and provide ecosystem services to support organic vegetable production. However, there is a risk of foodborne pathogen transfer to fresh produce because grazing may introduce enteric foodborne pathogens into the soil via animal feces, which may subsequently be transferred to the produce. Methods To examine the effect of cover crop use and the risk of cover crop grazing on the contamination of soil and produce by foodborne pathogens in ICLS, a three-year (2019–2021) experimental study was conducted in organically managed plots, which were assigned three different treatments (fallow without cover crop or grazing, cover crop without grazing, or cover crop with grazing by sheep) in a maize/tomato rotation. During the three years of the experiment, a total of 184 pre- and post-graze fecal samples and 96 samples of tomatoes were collected to test for foodborne pathogens (Escherichia coli O157, non-O157 Shiga toxin-producing Escherichia coli (STEC), and Listeria (L.) monocytogenes). Soil samples were collected monthly until 126–171 days after grazing (824 in total) to examine the presence of foodborne pathogens, and generic E. coli (MPN/g) was quantified to compare its persistence among the three treatments. Results and Discussion We did not detect any foodborne pathogens from harvested tomatoes in 2020 and 2021. One non-O157 STEC positive soil sample (0.1%, 1/824) was detected in the fallow treatment, and one L. monocytogenes-positive (1.1%, 1/92) was detected from the post-graze fecal samples. When assessing proportions of generic E. coli positive and counts of generic E. coli in the soil samples using mixed effect zero-inflated negative binomial models, soil samples collected in the graze cover crop treatment plot showed significant increases in the counts of generic E. coli until 61–82 days post grazing, but no difference was observed after 96–123 days, compared to the baseline of the fallow treatment. Findings from generic E. coli counts support the use of the United States Department of Agriculture (USDA) National Organic Program (NOP) 90- or 120-day interval rule between applying raw manure and harvesting in organic farming into ICLS. Additionally, we confirmed that commercial organic compost application before cover crop seeding in the winter had no significant effect on the proportions and counts of generic E. coli in the soil of the following growing seasons. This longitudinal field trial confirmed that the effect of sheep grazing on foodborne pathogen contamination in ICLS is minimal but further studies comparing the genetic associations between fecal and soil samples would be necessary to distinguish the source of foodborne pathogen contamination.